Growth and productivity of okra intercropped with kale in direct planting under organic management - Boes Sackser, Guilherme Augusto; de Moraes Echer, Márcia; Nepomuceno Alves , Thatiane; de Araújo Barbosa, Jaqueline; Hiromi Kiahara , Larissa; Pablo Wenderson Ribeiro Coutinho (Comunicata Scientiae, 2005)
The cultivation of vegetables in intercropping and direct planting are alternatives with greater economic, social and environmental efficiency. In this sense, the objective of this study was to evaluate the effect of different plant arrangement systems on the intercropping of okra and kale, as well as on the efficiency of use of the area. The experiment was conducted at the experimental station belonging to Unioeste, from May 2017 to March 2018 in direct planting, under organic management, using a randomized block design, containing seven treatments and four replications. The treatments consisted of the following arrangements of okra and kale plants in a consortium, T1 = three rows of kale with okra between the lines; T2 = three rows of kale with okra between the lines; T3 = three rows of kale with okra dense between the lines; T4 = three rows of kale with okra dense spaced between alternating lines; and monoculture T5 = three rows of kale; T6 = three rows of okra; T7 = three rows of dense okra. Assessments began 50 and 73 days after transplanting for kale and okra, respectively. Biometric and productivity variables were evaluated. The data were subjected to variance analysis and, when significant, regression analysis depending on the evaluation periods or compared using the Tukey test at 5% probability. It is concluded, that the okra crop showed greater productivity when grown in dense monoculture, and all intercropping systems promoted greater efficiency in land use.